The grassroots of a green revolution : polling America on the environment - Guber, Deborah Lynn (MIT Press, 2003)
Since the first Earth Day in 1970, environmentalism has become woven into the fabric of American life. Concern for environmental quality has influenced how we think, work, and recreate; what we buy; and how we govern. But popular consensus on the environment is more complicated than it appears. The real question is no longer whether Americans side with environmentalism, but the depth of their commitment. This book argues that understanding public opinion, the grassroots of the "green" revolution, is essential to sustaining genuine environmental progress. The long-term success of the environmental movement will be measured not only by its legislative achievements, but by its ability to persuade average citizens to back up their words with action and to further alter their voting patterns, buying habits, and lifestyles. The Grassroots of a Green Revolution uses polling data from a wide variety of sources to explore the myths, inconsistencies, and tensions that characterize public thinking on environmental issues. The book defines and describes key characteristics of public opinion, including direction, strength, stability, distribution, and consistency, and shows how those qualities influence behavior. The book uses that body of evidence to weigh the significance of environmental concern in U.S. politics and policy and to provide pragmatic advice for decision makers in their efforts to motivate Americans to act in an environmentally responsible way